Nucleolar Proteome Analysis and Proteasomal Activity Assays Reveal a Link between Nucleolus and 26S Proteasome in A. thaliana - Montacié, Charlotte; Durut, Nathalie; Opsomer, Alison; Palm, Denise; Comella, Pascale; Picart, Claire; Carpentier, Marie-Christine; Pontvianne, Frederic; Carapito, Christine; Schleiff, Enrico; Sáez-Vásquez, Julio (Frontiers in Plant Science, 2017)
In all eukaryotic cells, the nucleolus is functionally and structurally linked to rRNA synthesis and ribosome biogenesis. This compartment contains as well factors involved in other cellular activities, but the functional interconnection between non-ribosomal activities and the nucleolus (structure and function) still remains an open question. Here, we report a novel mass spectrometry analysis of isolated nucleoli from Arabidopsis thaliana plants using the FANoS (Fluorescence Assisted Nucleolus Sorting) strategy. We identified many ribosome biogenesis factors (RBF) and proteins non-related with ribosome biogenesis, in agreement with the recognized multi-functionality of the nucleolus. Interestingly, we found that 26S proteasome subunits localize in the nucleolus and demonstrated that proteasome activity and nucleolus organization are intimately linked to each other. Proteasome subunits form discrete foci in the disorganized nucleolus of nuc1.2 plants. Nuc1.2 protein extracts display reduced proteasome activity in vitro compared to WT protein extracts. Remarkably, proteasome activity in nuc1.2 is similar to proteasome activity in WT plants treated with proteasome inhibitors (MG132 or ALLN). Finally, we show that MG132 treatment induces disruption of nucleolar structures in WT but not in nuc1.2 plants. Altogether, our data suggest a functional interconnection between nucleolus structure and proteasome activity.